2019 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2019
DOI: 10.1109/vlhcc.2019.8818832
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Live-Streamed Programming

Abstract: Fig. 1: In live-streamed programming, a developer working on a programming activity shares a live video of their work with other developers, who may interact through chat to ask questions, suggest alternatives, and help find defects.Abstract-In live-streamed programming, developers broadcast their development work on open source projects using streaming media such as YouTube or Twitch. Sessions are first announced by a developer acting as the streamer, inviting other developers to join and interact as watchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Regarding the discipline and the methodology, Table 2 presents for each of the identified research subdomains the main approaches applied and the research areas in which the WoS indexes these documents. In the subdomain focused on the streamer, it can be seen that qualitative methods predominate, especially exploratory studies, interviews, or ethnographic methods [ 6 , 10 , 56 , 57 , 58 , 82 , 83 , 84 ], with samples ranging from 20 [ 6 ] to 100 interviews [ 57 , 58 , 82 ] and observational data from 20 to 70 hours of live streaming [ 56 , 85 ]. This may be partly due to the difficulty of obtaining a broad database with enough streamers to carry out the type of quantitative analysis that represents the traditional methodological approach in the predominant research area (communication).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the discipline and the methodology, Table 2 presents for each of the identified research subdomains the main approaches applied and the research areas in which the WoS indexes these documents. In the subdomain focused on the streamer, it can be seen that qualitative methods predominate, especially exploratory studies, interviews, or ethnographic methods [ 6 , 10 , 56 , 57 , 58 , 82 , 83 , 84 ], with samples ranging from 20 [ 6 ] to 100 interviews [ 57 , 58 , 82 ] and observational data from 20 to 70 hours of live streaming [ 56 , 85 ]. This may be partly due to the difficulty of obtaining a broad database with enough streamers to carry out the type of quantitative analysis that represents the traditional methodological approach in the predominant research area (communication).…”
Section: Resultsmentioning
confidence: 99%
“…This cluster includes studies focused on the different motivations that drive the audience [ 7 , 17 , 64 ] and content developers or streamers [ 53 , 54 , 85 ]. It also covers the characteristics, motivations for, and challenges of live-stream programming [ 85 ], new forms of paid work [ 6 , 10 , 55 , 56 , 57 , 58 , 83 ], user motivation [ 7 , 17 ], and identification between audience groups and streamers [ 65 ]. The relationships between the genre played, content streamed and viewer gratification [ 59 ], the motivations for spending money [ 104 ], and the relationships between the size of the channel and user motivation [ 61 ] are also explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of live viewers per session ranges from 5 to 500 people on average. Note that the two closest related prior works that focused on programming streams [4,15] had all male participants.…”
Section: Methodsmentioning
confidence: 99%
“…Alaboudi et al conducted a similar preliminary study that compared live streaming programming to pair programming by watching 20-hour stream archive videos and surveying five streamers [4]. They found that streamers struggled to balance between engaging with viewers and streaming the content, and viewers who joined the stream in the middle found it difficult to understand the stream content.…”
Section: Programming-focused Live Streamingmentioning
confidence: 99%